2000
DOI: 10.1016/s0020-7292(99)00195-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of spontaneous abortion in Bahrain before and after the Gulf War of 1991

Abstract: Several published reports from Iraq, Kuwait and now from Bahrain are suggestive of an increase in the incidence of abortion and adverse outcome of pregnancy after the Gulf War of 1991. The mechanism is not clear, i.e. whether this is affected by toxicity acquired through the food chain, the oil spillage, smoke pollution resulting from the burning of the Kuwaiti oil fields or stress and anxiety caused by the war.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
1
10
0
3
Order By: Relevance
“…Different stressful events, including war, may cause changes in some segments of perinatal outcome; increased abortion rate, low birth weight babies, increase in the number of stillbirths and pregnancy-induced hypertension and pre-eclampsia in war affected areas [1][2][3][4]. However, the influence of life stress on premature labor is controversial [5].…”
Section: Introductionmentioning
confidence: 99%
“…Different stressful events, including war, may cause changes in some segments of perinatal outcome; increased abortion rate, low birth weight babies, increase in the number of stillbirths and pregnancy-induced hypertension and pre-eclampsia in war affected areas [1][2][3][4]. However, the influence of life stress on premature labor is controversial [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rajab et al (2000) compare the incidence of spontaneous abortions in the 5 years before and the 5 years after the Gulf War based on hospital records from the main referral hospital of Bahrain, and find an increase in referrals in the post-war period. Using Chinese retrospective fertility histories data, Cai & Feng (2005) find that the probability of miscarriage and stillbirth increased in China during years corresponding to the Chinese Cultural Revolution and years corresponding to the famine caused by the Great Leap Forward, after controlling for a linear time trend and parental socioeconomic characteristics.…”
mentioning
confidence: 99%
“…However, pathologies and incompatibilities alone do not explain all miscarriages (12). Maternal stress is commonly cited as a potential cause for at least part of pregnancy losses that remain ''unexplained'' (13)(14)(15)(16)(17)(18)(19)(20)(21). Yet, for humans, little physiological evidence exists in support of this hypothesis (22)(23)(24).…”
mentioning
confidence: 99%
“…Previous research on the topic, however, has focused mainly on clinical pregnancy (Ͼ6 weeks after last menstrual period, equivalent to Ͼ4 weeks after conception) (23). Furthermore, except for studies on women with known fertility problems (22), past studies have rarely included physiologic measures (14)(15)(16)30). Whereas some previous studies found stress to be associated with spontaneous abortion (15,24,31,32), others did not (23,30).…”
mentioning
confidence: 99%